Awal Dakwah dan Historisitas Pra Islam Arabia - Indra Latif Syaepu; M. Sauki (Communicative : Jurnal Dakwah dan Komunikasi, 2020)
This article deals with the history of pre-Islam Arabia. It talks about, politics, economics, cultures and religions. It tries to explore the situation of the civilization which was decline, while the civilization of Arab rise up. Most of Arabia is the victim of natur amaligna. The geological process is responsible for its shape and outline, a huge quadric lateral placed between two continents. At the time, trading, breeding and farming was most populer in society south arabia and north-arabia, but in Hijaz (Mecca) was impossible because the area is wiped out. They believed on paganism, because Judism and Cristianity were not popular